The role of the color of the skin in the Antillais and French-speaking black sub-Saharan Africa contemporary novel - (:unkn) unknown (My University, 2014)
The contact with the Other, so called because of its cultural, skin color or phenotype difference, has generated a deep upheaval into the sociocultural structures and affected territories by the slave and colonial systems. Nowadays, the new generation natives of those territories are facing transformations that we are investigating in order to bring out the colonial survivals and the new sociological phenomena described by the contemporary French-speaking authors. The subjects analyzed by the latter in their works are expressing interactions based on ideological, racial, physical, cultural differences and/or similarities, in the three geographical areas: the Antilles (Martinique, Guadeloupe), Africa (black and French-speaking sub-Saharan) and Metropolitan France. The novel becomes then a dissection instrument of the effects of the presence and the domination of Western ideology and culture. Thereby, we discover the different types of relations, White/Black, former slave driver/former slave, former dominant/former dominated, former colonizer/former colonized, from the authors point of view. In a social context dominated by human movements and intercultural exchanges, the crossed looks of the characters focus on the various forms of otherness and identity and on the current problems in relation with race, immigration, exile, racism.
Keywords: African Research